2002
DOI: 10.1038/nn983
|View full text |Cite|
|
Sign up to set email alerts
|

Sonic hedgehog regulates adult neural progenitor proliferation in vitro and in vivo

Abstract: Neural stem cells exist in the developing and adult nervous systems of all mammals, but the basic mechanisms that control their behavior are not yet well understood. Here, we investigated the role of Sonic hedgehog (Shh), a factor vital for neural development, in regulating adult hippocampal neural stem cells. We found high expression of the Shh receptor Patched in both the adult rat hippocampus and neural progenitor cells isolated from this region. In addition, Shh elicited a strong, dose-dependent proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
599
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(632 citation statements)
references
References 50 publications
28
599
0
5
Order By: Relevance
“…Administration of glial cell line-derived neurotrophic factor after adult stroke results in less cell death and glial cell linederived neurotrophic factor stimulates subventricular zone neurogenesis and migration of precursor cells toward the site where new neurons are needed (49,50). Sonic hedgehog is a powerful factor that stimulates neural progenitor cell proliferation, migration, and differentiation toward neurons and oligodendrocytes and could thereby contribute to both gray and white matter remodeling (51).…”
Section: Growth-promoting Environmentmentioning
confidence: 99%
“…Administration of glial cell line-derived neurotrophic factor after adult stroke results in less cell death and glial cell linederived neurotrophic factor stimulates subventricular zone neurogenesis and migration of precursor cells toward the site where new neurons are needed (49,50). Sonic hedgehog is a powerful factor that stimulates neural progenitor cell proliferation, migration, and differentiation toward neurons and oligodendrocytes and could thereby contribute to both gray and white matter remodeling (51).…”
Section: Growth-promoting Environmentmentioning
confidence: 99%
“…The cell types that release Shh in the SGZ-GCL neurogenic niche are believed to be astrocytes (Jiao and Chen 2008). Pertaining to adult hippocampal neurogenesis, studies have shown that overexpression of Shh enhances SGZ-NSC proliferation and inhibition of Shh signaling decreases SGZ-NSC proliferation in the postnatal hippocampus (Lai et al 2003). Additional studies suggest that both quiescent NSCs and transit amplifying progenitor cells in the SGZ respond to Shh signaling and contribute to ongoing neurogenesis (Ahn and Joyner 2005;Jiao and Chen 2008).…”
Section: Expression Of Stat3 and Shh Genes Is Enhanced In The Aged Dgmentioning
confidence: 99%
“…[14][15][16][17] Shh is a secreted neurodifferentiation factor that binds to a receptor complex, patched (ptc)-smoothened (smo). Binding of Shh to ptc inhibits smo, an inhibitory receptor, 18 stimulating the transduction of the intracellular signaling pathway that leads to the activation of its main downstream transcriptional mediators, [19][20][21][22] that is, the transcription factor Gli1 23,24 ; these proteins are all present within the adult rodent brain.…”
Section: Introductionmentioning
confidence: 99%
“…ShhN protects cultures of fetal dopamine neurons from MPP+ toxicity, 28 and regulates the differentiation and proliferation of neuronal stem cells. 14,15,29 Further, Shh peptide injected directly into the brain of rodents and marmosets has beneficial effects in experimental models of Parkinson's disease. [30][31][32] We have recently demonstrated that adenoviral vectors encoding ShhN, or Gli1 under the control of pancellular viral promoters, have a neuroprotective effect on nigrostriatal dopaminergic neurons in an experimental model of dopamine neurodegeneration induced by 6-OHDA.…”
Section: Introductionmentioning
confidence: 99%